Beyond the buzz: insect-based foods are unlikely to significantly reduce meat consumption - Corentin Biteau; Tom Bry-Chevalier; Dustin Crummett; Ren Ryba; Michael St. Jules (npj Sustainable Agriculture)
Abstract The substantial environmental footprint of meat production means that dietary shifts are needed to reduce greenhouse gas emissions. Insects may offer one alternative, but must first be widely accepted and consumed by the general public. This review evaluates the prospects of insect-based foods to compete with meat. We find that insect-based foods face major challenges, including low consumer acceptance and limited investment. They have a low likelihood of significantly reducing meat consumption, particularly when compared to more accepted plant-based alternatives.